Survey method matters: Online/offline questionnaires and face-to-face or telephone interviews differ. (June 2017) - Zhang, XiaoChi; Kuchinke, Lars; Woud, Marcella L.; Velten, Julia; Margraf, Jürgen
Abstract: Self-report inventories enable efficient assessment of mental attributes in large representative surveys. However, an inventory can be administered in several ways whose equivalence is largely untested. In the present study, we administered thirteen psychological questionnaires assessing positive and negative aspects of mental health. The questionnaires were administered by four different data collection methods: face-to-face interview, telephone interview, online questionnaire, and offline questionnaire. We found that twelve of the questionnaires differed in survey methods. Although, some studies showed that social desirability tends to be highest for telephone survey and lowest for web survey. Furthermore, the effects of social desirability should be the same for the online and offline samples. However, there were no statistically significant differences between the face-to-face and telephone samples for the anxiety scale, the stress scale, and the tradition scale. We also found that for eight scales, the online sample was statistically different from the offline sample in the respondent answers. Moreover, the survey method effects were only moderated by age. Finally, measurement invariance across the four survey methods was tested for each self-report measure. There was full strong measurement invariance established for nine of thirteen scales and partial strong measurement invariance for the remaining four scales across the four survey methods. These findings indicated that measurement invariance was affected by different survey methods. Highlights: Face-to-face and Telephone samples yielded same results for three scales. Online and Offline samples yielded different results for eight scales. Measurement invariance was affected by different survey methods.